Improving the Local Economy of the Community Thru Land Utilization for Livestock Farming - Abdillah Arif Nasution; Aulia Arif Nasution (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2026)
Halaban Village, located in Besitang District, Langkat Regency, has great potential in the agricultural and livestock sectors, but still faces various challenges in developing sustainable livestock businesses. The main problems faced by the community are limited capital, low managerial skills, and dependence on wage labor. The community service program by the University of North Sumatra (USU) aims to improve the local economy by empowering communities in the field of animal husbandry. The approach used includes managerial training, providing capital in the form of breeding stock and developing livestock business infrastructure, as well as ongoing mentoring to strengthen entrepreneurial skills. The results of this program show an improvement in the community's ability to manage livestock businesses and financial records, as well as significant social changes, such as an increase in collective work spirit. Nevertheless, there are still challenges in managerial consistency and the division of tasks among members. This program is expected to strengthen the economic independence of the people of Halaban Village and serve as a model for community empowerment based on agribusiness that can be applied in other villages.